The Short-Run Macroeconomics of Aid Inflows : Understanding the Interaction of Fiscal and Reserve Policy - Zanna, Luis-Felipe (IMF Working Papers; Working Paper ;, 2010)
We develop a tractable open-economy new-Keynesian model with two sectors to analyze the short-term effects of aid-financed fiscal expansions. We distinguish between spending the aid, which is under the control of the fiscal authorities, and absorbing the aid-using the aid to finance a higher current account deficit-which is influenced by the central bank's reserves policy when access to international capital markets is limited. The standard treatment of the transfer problem implicitly assumes spending equals absorption. Here, in contrast, a policy mix that results in spending but not absorbing the aid generates demand pressures and results in an increase in real interest rates. It can also lead to a temporary real depreciation if demand pressures are strong enough to threaten external balance. Certain features of low income countries, such as limited participation in domestic financial markets, make a real depreciation more likely by amplifying demand pressures when aid is spent but not absorbed. The results from our model can help understand the recent experience of Uganda, which saw an increase in government spending following a surge in aid yet experienced a real depreciation and an increase in real interest rates.